Outcomes with intensive treatment for acute myeloid leukemia: an analysis of two decades of data from the HARMONY Alliance - Sobas, Marta Anna; Turki, Amin T; Ramiro, Angela Villaverde; Hernández-Sánchez, Alberto; Elicegui, Javier Martinez; González, Teresa; Melchor, Raúl Azibeiro; Abáigar, María; Tur, Laura; Dall'Olio, Daniele; Sträng, Eric; Tettero, Jesse M; et al. (Haematologica, 2025)
Since 2017, targeted therapies combined with conventional intensive chemotherapy have started to improve outcomes of patients with acute myeloid leukemia (AML). However, even before these innovations, outcomes with intensive chemotherapy had improved, which has not yet been extensively studied. Thus, we used a large pan-European multicenter dataset of the HARMONY Alliance to evaluate treatment-time dependent outcomes over two decades. In 5,359 AML patients, we compared the impact of intensive induction therapy on outcome over four consecutive 5-year calendar periods from 1997 to 2016. During that time, the 5-year survival of AML patients improved significantly, also across different genetic risk groups. In particular, the 60-day mortality rate dropped from 13.0% to 4.7% over time. The independent effect of calendar periods on outcome was confirmed in multivariate models. Improvements were documented both for patients <60 and ≥60 years old, and in those treated with and without consolidating allogeneic hematopoietic stem cell transplantation (alloHCT). While survival of AML elderly patients remains poor, patients ≥60 years old overall have a 20% survival benefit at 5 years if they receive an alloHCT. While further outcome improvement in intensively treated AML patients will likely be driven by targeted treatment approaches, this pan-European HARMONY dataset can serve as a multicenter comparator for future studies.
Keywords: výsledek terapie; Young Adult; Hematopoietic Stem Cell Transplantation; Male; Antineoplastic Combined Chemotherapy Protocols; mladý dospělý; Adolescent; prognóza; Europe; Adult; transplantace hematopoetických kmenových buněk; akutní myeloidní leukemie; Aged; dospělí; mužské pohlaví; senioři; mladiství; Treatment Outcome; Evropa; senioři nad 80 let; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; Aged, 80 and over; Prognosis; Female; lidé středního věku; Leukemia, Myeloid, Acute; Middle Aged